2007
DOI: 10.1007/s11430-007-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-stratigraphic frameworks and their palaeogeographic patterns for the Permian Lopingian of the Dianqiangui Basin and its adjacent areas of Southwestern China

Abstract: The Permian Lopingian in the Dianqiangui Basin and its adjacent areas is marked by the coal measures of the Wuchiapingian and the carbonate strata of the Changhsingian stages. For the Lopingian of the Dianqiangui Basin and its adjacent areas, the diversity of sedimentary facies and the obviousness of facies change provide an advantaged condition on a study of sequence stratigraphy. Approximately, the Wuchiapingian stage constitutes a third-order sequence and the Changhsingian stage forms another. For the Wuchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The Triassic sediments in this region are characterized by transitions from a Lower Triassic starved basin with pelagic carbonate and shale and local shallow marine carbonate platform deposits, to Middle and Upper Triassic deep marine siliciclastic turbidites deposited during rapid subsidence, followed by continental clastic deposition (Lehrmann et al, 2005(Lehrmann et al, , 2015. These strata were subsequently deformed into a WNW-striking fold-thrust belt followed by the superposition of NNE-striking folds (Huang et al, 2013;Mei et al, 2003Mei et al, , 2007Mei et al, , 2001Minzoni, 2007;Wang et al, 2013;Yan et al, 2006). Previous studies, focusing on the formation, depositional history, sedimentary provenance and tectonic evolution (e.g., Duan et al, 2018;Faure et al, 2016bFaure et al, , 2016aHu et al, 2017;Liu et al, 2018;Qiu et al, 2017), have revealed several deformation episodes (e.g., Early Paleozoic Kwangsian, Triassic Indosinian, and Jurassic to Cretaceous Yanshanian events) and magmatic events in the Nanpanjiang region (Faure et al, 2014;Li et al, 2016Li et al, , 2014Qiu et al, 2016;Shu et al, 2009;Wang et al, 2018;Wang, Fan, Zhao, et al, 2007;Wu et al, 2019;Yang et al, 2018).…”
mentioning
confidence: 99%
“…The Triassic sediments in this region are characterized by transitions from a Lower Triassic starved basin with pelagic carbonate and shale and local shallow marine carbonate platform deposits, to Middle and Upper Triassic deep marine siliciclastic turbidites deposited during rapid subsidence, followed by continental clastic deposition (Lehrmann et al, 2005(Lehrmann et al, , 2015. These strata were subsequently deformed into a WNW-striking fold-thrust belt followed by the superposition of NNE-striking folds (Huang et al, 2013;Mei et al, 2003Mei et al, , 2007Mei et al, , 2001Minzoni, 2007;Wang et al, 2013;Yan et al, 2006). Previous studies, focusing on the formation, depositional history, sedimentary provenance and tectonic evolution (e.g., Duan et al, 2018;Faure et al, 2016bFaure et al, , 2016aHu et al, 2017;Liu et al, 2018;Qiu et al, 2017), have revealed several deformation episodes (e.g., Early Paleozoic Kwangsian, Triassic Indosinian, and Jurassic to Cretaceous Yanshanian events) and magmatic events in the Nanpanjiang region (Faure et al, 2014;Li et al, 2016Li et al, , 2014Qiu et al, 2016;Shu et al, 2009;Wang et al, 2018;Wang, Fan, Zhao, et al, 2007;Wu et al, 2019;Yang et al, 2018).…”
mentioning
confidence: 99%
“…Along with the following intensive investigations and studies, this sedimentary sequence had been divided into two parts. The upper part is mainly continental coal-bearing sandy shale (Chen et al, 2003;Mei et al, 2007), whereas the lower part consists of coal-bearing clastic rocks covered by ancient weathered crusts on the surface with different thicknesses that unconformably covered the Emeishan Basalts (Huang, 1997;Wang et al, 2006). On the geological sections, weathered basaltic and tuffaceous rocks were found, and also some typical mineralization of iron and copper was observed, which was considered as being related to strong weathering after the eruption of the Emeishan Basalts (Geological Team 108, Guizhou Bureau of Geology and Mineral Resources, 1973;Yang et al, 2008;Yang et al, 2011).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Siliciclastic facies, 1e2 Z Feixianguan Formation, carbonate facies; 3e5 Z Daye Formation, shelf facies; 6 Z Luolou and Qingyan formations. The south is part of the Dianqiangui or Nanpanjiang Basin (Mei and Tucker, 2007;. marked by a set of limestones with some oolitic grainstones in its upper part.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…(1) The basal boundary of DS 1 equates to a clear drowningunconformity, exhibited by basin siliceous rocks of the Permian Dalong Formation that lie directly over high-stand carbonates of the Upper Permian Changxing Formation (Schlager, 1989(Schlager, , 1999Chen, 1995;Hallam and Wignall, 1999;Mei and Tucker, 2007;; this larger-scale rapid transgression that occurred at the turn of the Permian to the Triassic, formed an upward-shallowing succession of sedimentary facies from basin to shallow ramp making up DS 1 ; (2) An abrupt transfer boundary of sedimentary facies from shallow to deep ramp in the middle part of the Daye Formation forms the basal boundary of DS 2 , which is marked by a transitional type of sequence-stratigraphic boundary as defined by Vail et al (1977), and an exposure-punctuated surface formed in the lower part of the Jialingjiang Formation, which is similar to the type-II sequence-stratigraphic boundary defined by Vail et al (1977), between which an upward-shallowing succession of sedimentary facies from deep ramp to top oolitic-bank constitutes DS 2 . Consequently, a set of oolitic-bank limestones with a thickness of about 50 m makes up the early high-stand system tract (EHST), and a set of dolomites with some dolomitic limestones and few oolites belonging to the lower Jialingjiang Formation makes up a forced-regressive wedge system tract (or late high-stand system tract (LHST); Hunt and Tucker, 1992) of the thirdorder sequence DS 2 .…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation